UI/UX Design of a Web-Based Bag Sales Information System Using the Waterfall Method and Usability Evaluation with SUS: A Case Study of Carrefour Bag MSME - Meilanie Kirana; Asto Purwanto (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
The growing adoption of information technology has pushed many Micro, Small, and Medium Enterprises (MSMEs) to shift from manual to digital-based sales management. Despite this trend, a considerable number of MSMEs continue to rely on manual recording systems, which often lead to transaction errors, inaccurate data, and limited capacity for product information display. This study aims to design the UI/UX of a web-based bag sales information system for Carrefour Bag MSME to improve sales management efficiency and user experience. The system was developed using the Waterfall method, covering four stages: requirements analysis, system design, implementation, and evaluation. Key features include user authentication, dashboard, product management, shopping cart, checkout, sales transactions, and sales reporting. The interface was designed to be simple, modern, and accessible for both administrators and customers. Usability was evaluated using the System Usability Scale (SUS) involving 30 respondents, yielding a mean SUS score of 86.6, which falls within the Excellent category. These results indicate that the system meets acceptable usability standards and is suitable for implementation at Carrefour Bag MSME to support more efficient and effective sales operations.